DISTRIBUTION OF PLASMODIUM SPOROZOITES IN ANOPHELINE MOSQUITO VECTORS IN SOME AREAS OF KATSINA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Control of malaria is highly dependent on accurate identification of Plasmodium species infecting, because of their variability in terms of sensitivity to drugs and susceptibility to the immune system. Therefore a survey of plasmodium species present in Katsina State was carried out from 2009 to 2014 to determine the distribution of Plasmodium sporozoites in Anopheline mosquito vectors in some areas of Katsina State, Nigeria. Anopheles mosquitoes were caught indoors using the Pyrethrin spray sheet method and were subjected to VecTest, using Dipstick assay. Zone A (Southern Katsina) recorded more P. falciparum and P. malariae than Zone B (Central Katsina) which in turn recorded more than Zone C (Northern Katsina). P. falcifarum was the most preponderant in Zone A, having the highest of 163 at Dandume and its lowest was 40 at Daura.  There was no significant difference between P. falciparum and P. malariae within the zones (p
Keywords: Distribution, abundance, plasmodium, sporozoites, VecTest, Dipstick assay